Validation of the Satisfaction with Life Scale in Peruvian workers - Calderón-De la Cruz, Gustavo (2018)
This paper presents the validation of the Satisfaction with Life Scale (SWLS). Participants were 177 workers (74% males) between 19 and 64 years of age (M = 36.24, SD = 9.75) from fishing companies located in different cities of Peru. Evidence of validity related to the internal structure was obtained through the confirmatory factor analysis complemented with the analysis of the average variance that determines the internal convergence between the items. In addition, evidence of validity was examined to assess its relationship with other constructs: the satisfaction with life fulfilled the role of dependent variable versus the effects of the burnout syndrome. The reliability of the internal consistency was calculated with Cronbach’s alpha coefficient, McDonald’s omega coefficient, and Mueller & Hancock ́s H coefficient. The results demonstrate a one-dimensional structure of the SWLS with errors correlated between pairs 1-2 and 4-5. In the regression analysis, the dimensions «professional efficacy» and «emotional exhaustion of burnout syndrome» influenced the «satisfaction with life» dimension in contrast to the «indifference» dimension. The internal consistency of the SWLS scores was acceptable. The implication of the results at practical and theoretical level is discussed, as well as the limitations and future recommendations.